2004
DOI: 10.1590/s1519-69842004000500016
|View full text |Cite
|
Sign up to set email alerts
|

Flooded native pastures of the northern region of the Pantanal of Mato Grosso: biomass and primary productivity variations

Abstract: The Pantanal comprises a number of landscape units, submitted to a flood pulse with variable intensity or regularity. One of these units, the flooded plains, is important in cattle raising. This study was carried out in the northern portion of the Pantanal and presents data related to the productive dynamics of the flooded native pastures both protected from and exposed to cattle. The greatest total biomass values were for the protected pasture due to accumulated dead biomass. Net primary production presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
3
10
0
2
Order By: Relevance
“…In the rainy season, plants in the sun have a higher net photosynthetic rate than shaded plants, possible due to a higher sink demand (growth) and leaf acclimation. Greater growth rates and carbon absorption were observed during the rainy season, characterized by higher temperatures, as previously reported in the literature, including studies from Brazil (Pozer and Nogueira, 2004;Silva et al, 2004). In coffee plants, Silva et al (2004) found an increased growth rate of plants, higher net carbon absorption during the months of October to March (rainy season) and a reduction in during the months of April to September (dry season).…”
Section: Discussionsupporting
confidence: 80%
“…In the rainy season, plants in the sun have a higher net photosynthetic rate than shaded plants, possible due to a higher sink demand (growth) and leaf acclimation. Greater growth rates and carbon absorption were observed during the rainy season, characterized by higher temperatures, as previously reported in the literature, including studies from Brazil (Pozer and Nogueira, 2004;Silva et al, 2004). In coffee plants, Silva et al (2004) found an increased growth rate of plants, higher net carbon absorption during the months of October to March (rainy season) and a reduction in during the months of April to September (dry season).…”
Section: Discussionsupporting
confidence: 80%
“…The DW values are expressed in grams per square meter (g DW.m -2 ). Net primary production (NPP) was determined according to Tieszen (1989) and Pozer and Nogueira (2004). According to this method, macrophyte productivity is calculated by determining the biomass difference between two consecutive samples and dividing this difference by the time in days between the two samples.…”
Section: Resultsmentioning
confidence: 99%
“…A família com maior riqueza de espécies nos CM do PEA (Poaceae) vem sendo citada como importante no Bioma (Pozer & Nogueira 2004).…”
Section: Discussionunclassified